A modelling investigation of solute transport in permeable porous media containing a discrete preferential flow feature. (August 2016) - Sebben, Megan L.; Werner, Adrian D.
Highlights: We simulate solute transport in permeable rock containing a discrete PFF. More dispersed solute plumes are displaced further than less dispersed plumes. Lateral extents of plumes intercepting a PFF are likely to be greater than in PMO. Plume asymmetry across a PFF is more pronounced for more dispersive plumes. Abstract: Preferential flow features (PFFs, e.g. fractures and faults) are common features in rocks that otherwise have significant matrix permeability. Despite this, few studies have explored the influence of a PFF on the distribution of solute plumes in permeable rock formations, and the current understanding of PFF effects on solute plumes is based almost entirely on low-permeability rock matrices. This research uses numerical modelling to examine solute plumes that pass through a PFF in permeable rock, to explore the PFF's influence on plume migration. The study adopts intentionally simplified arrangements involving steady-state solute plumes in idealised, moderate-to-high-permeability rock aquifers containing a single PFF. A range of matrix-PFF permeability ratios (4.9 × 10 −6 –2.5 × 10 −2 ), typical of fractured sedimentary aquifers, is considered. The results indicate that for conditions representative of high-to-moderate-permeability sedimentary rock matrices containing a medium-sized fracture, the effect of the PFF on solute plume displacement and spreading can be considerable. For example, plumes are between 1.3 and 19 times wider than in associated porous media only scenarios, and medium-sized PFFs in moderately permeable matrices can reduce the maximum solute concentration by up to 10 4 times. Plume displacement and spreading is lower in aquifers of higher matrix-PFF permeability ratios, and where solute plumes are more dispersed at the point of intersection with the PFF. Asymmetry in the plume caused by the passage through the PFF is more pronounced for more dispersive plumes. The current study demonstrates that PFFs most likely govern solute plume characteristics in typical permeable matrices, given that a single PFF of aperture representing a medium-sized fracture (i.e. 5.0 × 10 −4  m) produces the equivalent spreading effects of 0.22–7.88 m of plume movement through the permeable matrix.